2005
DOI: 10.4049/jimmunol.174.2.1097
|View full text |Cite
|
Sign up to set email alerts
|

Lipoprotein I, a TLR2/4 Ligand Modulates Th2-Driven Allergic Immune Responses

Abstract: Asthma is an inflammatory lung disease that is initiated and directed by Th2 and inhibited by Th1 cytokines. Microbial infections have been shown to prevent allergic responses by inducing the secretion of the Th1 cytokines IL-12 and IFN-γ. In this study, we examined whether administration of lipoprotein I (OprI) from Pseudomonas aeruginosa could prevent the inflammatory and physiological manifestations of asthma in a murine model of OVA-induced allergic asthma. OprI triggered dendritic cells to make IL-12 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
62
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 95 publications
(68 citation statements)
references
References 36 publications
5
62
1
Order By: Relevance
“…Previous studies have evaluated the effect of TLR2 signaling on allergic diseases, but the results are conflicting. In our model, triggering of TLR2 with Pam3CSK4 showed a beneficial antiallergic effect on allergic rhinitis, which is consistent with several pre- vious studies (Akdis et al, 2003;Patel et al, 2005;Revets et al, 2005). The mechanism of its antiallergic effect is still elusive.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Previous studies have evaluated the effect of TLR2 signaling on allergic diseases, but the results are conflicting. In our model, triggering of TLR2 with Pam3CSK4 showed a beneficial antiallergic effect on allergic rhinitis, which is consistent with several pre- vious studies (Akdis et al, 2003;Patel et al, 2005;Revets et al, 2005). The mechanism of its antiallergic effect is still elusive.…”
Section: Discussionsupporting
confidence: 75%
“…Studies in TLR4 signaling showed that stimulation of TLR4 by relatively high dose of lipopolysaccharide reduced allergic inflam-mation in a murine model of asthma (Rodriguez et al, 2003). However, the role of TLR2 signaling in allergy remains controversial, since several studies reported that TLR2 ligands administered to murine models of allergy during the sensitization period led to an enhancement of Th2-mediated allergic inflammation (Chisholm et al, 2004;Redecke et al, 2004), while others showed TLR2 activation with its ligands suppressed Th2-type responses and IgE production in animal models either before or after airway allergen challenge (Patel et al, 2005;Revets et al, 2005). TLR2 recognizes components from a variety of microorganisms including lipoproteins, peptidoglycan and lipoteichoic acid mainly from Gram-negative bacteria.…”
Section: Introductionmentioning
confidence: 99%
“…However, the concern is that whole pathogens might also induce the production of proinflammatory cytokines through TLR ligation, the extent of which will determine whether downregulation of allergic responses or pathology ensues. Indeed, probiotic not only induce IL-10 production, but they also increase the production of IFN-c (80) or they induce the production of IFN-c alone (52,53), thus again supporting the concept that their preventive activity on the development of allergic reactions is mediated by a combined mechanism of immune suppression and immune deviation or perhaps by immune deviation alone. An exception to the rule that bacteria or their components do induce immune deviation rather than immune suppression seems to be Mycobacterium vaccae, whose administration during allergen sensitization or challenge suppressed asthmatic features by mediating allergen-specific Treg cells to produce both IL-10 and TGF-b (81).…”
Section: Possible Regulation Of Th2 Cell-mediated Inflammation By Immmentioning
confidence: 78%
“…with 10 g of chicken egg albumin (OVA) (SigmaAldrich) bound to 1 mg of aluminum hydroxide (Type V; Sigma-Aldrich) suspended in 0.5 cc of PBS (Mediatech) on days 0 and 7. This preparation of OVA has been shown to have Ͻ1 U of endotoxin per milligram of OVA (25). Mice underwent aerosol challenge with nebulized OVA (10 mg/ml in PBS) or with PBS alone on days 14 -16.…”
Section: Mouse Modelsmentioning
confidence: 99%